The impact of ageing on adipose structure, function and vasculature in the B6D2F1 mouse: evidence of significant multisystem dysfunction. (15th September 2014) - Donato, Anthony J.; Henson, Grant D.; Hart, Corey R.; Layec, Gwenael; Trinity, Joel D.; Bramwell, R. Colton; Enz, Ryley A.; Morgan, R. Garrett; Reihl, Kelly D.; Hazra, Sugata; Walker, Ashley E.; Richardson, Russell S.; et al.
Abstract : Key points: Dysfunction in the adipose tissue, characterized by reduced adipocyte size, tissue fibrosis and ectopic lipid accumulation, has been implicated in age‐associated metabolic dysfunction, but it is not known how ageing affects the function of the arteries and mitochondria within the adipose tissue. Mitochondrial lipid utilization is impaired in adipose tissue of old mice, evidenced by reduced substrate control ratios in the presence of lipid substrates and is concomitant with increased oxidative stress. Ageing leads to endothelial dysfunction, evidenced by reduced endothelium‐dependent dilation in resistance arteries, reduced angiogenic capacity and reduced vascularity of the adipose tissue. These results indicate that arterial and mitochondrial dysfunction accompany age‐associated adipose tissue and systemic metabolic dysfunction and suggest that targeting arterial or mitochondrial function to improve adipose tissue function may have important application in the treatment of age‐associated metabolic dysfunction. Abstract: The critical influence of the white adipose tissue (WAT) on metabolism is well‐appreciated in obesity, but adipose tissue dysfunction as a mechanism underlying age‐associated metabolic dysfunction requires elucidation. To explore this possibility, we assessed metabolism and measures of epididymal (e)WAT mitochondria and artery function in young (6.1 ± 0.4 months) and old (29.6 ± 0.2 months) B6D2F1 mice. There were no group differences in average daily oxygen consumption, fasted blood glucose or plasma free fatty acids, but fasted plasma insulin and the homeostatic model assessment of insulin resistance (HOMA‐IR%) were higher in the old (∼50–85%, P < 0.05). Tissue mass ( P < 0.05) and adipocyte area were lower (∼60%) ( P < 0.01) and fibrosis was greater (sevenfold, P < 0.01) in eWAT with older age. The old also exhibited greater liver triglycerides (∼60%, P < 0.05). The mitochondrial respiratory oxygen flux after the addition of glutamate and malate (GM), adenosine diphosphate (d), succinate (S) and octanoyl carnitine (O) were one‐ to twofold higher in eWAT of old mice ( P < 0.05). Despite no change in the respiratory control ratio, substrate control ratios of GMOd /GMd and GMOSd /GMd were ∼30–40% lower in old mice ( P < 0.05) and were concomitant with increased nitrotyrosine ( P < 0.05) and reduced expression of brown adipose markers ( P < 0.05). Ageing reduced vascularity (∼50%, P < 0.01), angiogenic capacity (twofold, P < 0.05) and expression of vascular endothelial growth factor (∼50%, P < 0.05) in eWAT. Finally, endothelium‐dependent dilation was lower ( P < 0.01) in isolated arteries from eWAT arteries of the old mice. Thus, metabolic dysfunction with advancing age occurs in concert with dysfunction in the adipose tissue characterized by both mitochondrial and arterial dysfunction.